Molecular Diagnostics of Histoplasmosis - A. V. Lipnitsky; A. M. Markin; R. S. Surkova; D. V. Victorov; A. V. Toporkov (Проблемы особо опасных инфекций, 2019)
Histoplasmosis is a systemic fungal disease that occurs worldwide. The highest incidence of the disease is reported on the American continent. It also occurs in China, India, South-Eastern Asia, Africa, Australia and Europe. Clinical syndromes of histoplasmosis are not specific and in most cases immunocompetent individuals are asymptomatic or present mild influenza-like disease. Immunocompromised patients especially individuals with AIDS, can develop a severe and fatal disease due to fungal dissemination to many organs. Etiological agent of histoplasmosis is the dimorphic fungus Histoplasma capsulatum, which inhabits the soils contaminated with bird or bat droppings. Three biological varieties are considered for this fungus: H. capsulatum var. capsulatum, H. capsulatum var. duboissii and H. capsulatum var. farciminosum. Genetic differences are observed among H. capsulatum strains from diverse regions of the world. The main molecular methodologies for genetic typing of fungi are based on DNA fingerprinting. They have been an important instrument to identify possible sources of infection in outbreaks of histoplasmosis. Genetic profiles of H. capsulatum, isolated from bats and humans, helped to understand the distribution of the disease in certain endemic regions. The con-ventional diagnosis of histoplasmosis is performed by means of cultural and microscopic examination of samples from the respiratory tract and biologic fluids. However, these techniques yield positive results in only 50 % of cases. In the last two decades, approaches for the detecting of H. capsulatum in clinical samples, using different molecular targets, based on PCR assay have been developed. Their use can shorten the time span of analysis for diagnosis confirmation. Molecular methods have high specificity and sensitivity and reduce the risk of infection for the laboratory personnel. In this study we reviewed the recently published data on the use of main molecular methods for diagnosis of histoplasmosis.